Unpacking the Evolution of Learning Organization in Public Institutions: Trends, Themes, and Future Directions - Mufti, Hafidz; Desiana, Putri Mega (APMBA (Asia Pacific Management and Business Application), 2025)
This study maps five decades of research on learning organizations (LOs) within public institutions, aiming to trace their conceptual evolution, identify dominant themes, and outline directions for future inquiry. Drawing on 34 peer-reviewed studies published between 1971 and 2025, the analysis integrates bibliometric and thematic synthesis to capture trends in publication, theoretical frameworks, and methodological approaches. The findings indicate a shift from static, one-size-fits-all models toward dynamic, context-sensitive frameworks that interweave leadership, organizational culture, technology, and governance. Studies emphasise that transformational leadership and adaptive learning cultures foster innovation and performance improvement, while digital transformation presents both enablers and constraints for learning processes. Despite the growing diversity of research contexts, the field remains concentrated in high-income countries, with limited evidence from developing economies. Literature calls for more empirical, longitudinal, and cross-regional research capable of contextualising learning organization practices within political, cultural, and digital realities of public administration. The paper concludes by providing an evolutionary mapping of the learning organization literature in public administration that connects knowledge management, digital maturity, and leadership adaptability as critical components of future public-sector learning organizations.